Respuesta :

8(t + 2) - 3(t - 4) = 6(t - 7) + 8

To solve this equation, first apply the Distributive Property. The Distributive Property is defined as a(b + c) = ab + ac. We'll need to apply it three times for this equation.

    8(t + 2)  =>  8t + 16
    -3(t - 4)  =>  -3t + 12
     6(t - 7)  =>  6t - 42

This gives us

    
8(t + 2) - 3(t - 4) = 6(t - 7) + 8
    8t + 16 - 3t + 12 = 6t - 42 + 8

Next, combine like terms (constants with constants and variable terms with variable terms).

    8t + 16 - 3t + 12 = 6t - 42 + 8
                  5t + 28 = 6t - 34

Now we need to get all constants on one side and all variable terms on the other side. Begin doing so by first subtracting 28 from both sides.

    5t + 28 = 6t - 34
            5t = 6t - 62

Subtract 6t from both sides.

    5t = 6t - 62
     -t = -62

Divide both sides by -1.

    t = 62

Answer:
t = 62
ACCESS MORE